An Analysis of Teacher’s Directive Speech Act in Learning English at SMKN 2 Mataram - Muhammad Romzi; Dewi, Puspita; Hadi, Muhammad Zaki Pahrul (Jurnal Ilmu Sosial dan Humaniora, 2023)
This research aims to identify the types of directive speech acts, the directive speech act strategies, and the types of directive speech act that are most widely used by English teachers at SMKN 2 Mataram. The research method used is the mixed method. The source of the data in this study was one of the teachers who taught English at SMKN 2 Mataram majoring in the Tourism Industry. Data were obtained from spoken sources, by listening to the teacher's speech acts to students in the learning process in the classroom. The data collection techniques used in this study are SLBC, the recording technique, and the note-taking/transcript technique. The technique of analyzing data uses 3 ways, namely: reduce data, display data, and draw or verify data. The research results show that there are 5 types of directive speech acts, namely directive speech telling 31.65%, asking 27.85%, suggesting 8.86%, Advising 10.76%, and Challenging 20.89%. Furthermore, there are 2 speech strategies, namely direct 96.30% and indirect 3.70%. Telling is the highest percentage of the types of directive speech acts used by teachers, even though what should be needed is other types of directive speech acts. Because based on many studies, directive telling has little effect on providing understanding to students in the learning process. The results of this study are expected to contribute to teachers being able to convey various directive speech acts in the classroom with the right strategy in the learning process. Therefore, the teacher's speech acts must be able to direct students to the learning process.